(untitled) (ZAMONAVIY TARAQQIYOT VA FAN: 21-ASR YONDASHUVLARI, 2025)
The study examines how teachers can balance authority and emotional connection with students, maintaining respect without crossing personal boundaries. Focusing on mental well-being and ethical teaching, it uses observation and interviews to show that empathy combined with professionalism builds trust and improves teaching effectiveness.